2000
DOI: 10.1016/s0893-133x(00)00118-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Lead Exposure Alters the Stimulatory Properties of Cocaine at PND 30 and PND 90 in the Rat

Abstract: The aim of this study was to examine the effects of perinatal lead exposure on locomotor responding following acute and repeated cocaine challenges (sensitization).Lead poisoning continues to present major health concerns nationwide, and this situation is especially problematic among children. Recent sociodemographic data indicate the threat of lead toxicity is especially great among economically disadvantaged, nonwhite, and inner-city children (Goldman and Carra 1994;Pirkle et al. 1994). Along these lines, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
5
17
0
1
Order By: Relevance
“…Likewise, other studies using animal models have reported that developmental exposure to lead (Clifford et al, 2011; D. K. Miller, Nation, & Bratton, 2000, 2001; Nation, Miller, & Bratton, 2000), cadmium (Nation & Miller, 1999), manganese (Guilarte et al, 2008; McDougall et al, 2008; Reichel et al, 2006), and methylmercury (Eccles & Annau, 1982; Newland, Reed, & Rasmussen, 2015; Rasmussen & Newland, 2001; Reed et al, 2008; Wagner, Reuhl, Ming, & Halladay, 2007) alter dopamine neurotransmission and alter the response to experimenter -administered psychostimulants during adulthood, often in a sex-specific manner. This is the first study to demonstrate that rats perinatally exposed to PCBs exhibit differences in the propensity to acquire self -administration of cocaine and is one of a handful of other studies demonstrating monoamine-disrupting environmental contaminants such as lead (Nation, Cardon, Heard, Valles, & Bratton, 2003; Nation, Smith, & Bratton, 2004; Rocha, Valles, Bratton, & Nation, 2008; Rocha, Valles, Cardon, Bratton, & Nation, 2005; Rocha, Valles, Hart, Bratton, & Nation, 2008; Valles, Rocha, Cardon, Bratton, & Nation, 2005) and cadmium (Cardon, Rocha, Valles, Bratton, & Nation, 2004) can also alter psychostimulant self-administration in adulthood after perinatal exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, other studies using animal models have reported that developmental exposure to lead (Clifford et al, 2011; D. K. Miller, Nation, & Bratton, 2000, 2001; Nation, Miller, & Bratton, 2000), cadmium (Nation & Miller, 1999), manganese (Guilarte et al, 2008; McDougall et al, 2008; Reichel et al, 2006), and methylmercury (Eccles & Annau, 1982; Newland, Reed, & Rasmussen, 2015; Rasmussen & Newland, 2001; Reed et al, 2008; Wagner, Reuhl, Ming, & Halladay, 2007) alter dopamine neurotransmission and alter the response to experimenter -administered psychostimulants during adulthood, often in a sex-specific manner. This is the first study to demonstrate that rats perinatally exposed to PCBs exhibit differences in the propensity to acquire self -administration of cocaine and is one of a handful of other studies demonstrating monoamine-disrupting environmental contaminants such as lead (Nation, Cardon, Heard, Valles, & Bratton, 2003; Nation, Smith, & Bratton, 2004; Rocha, Valles, Bratton, & Nation, 2008; Rocha, Valles, Cardon, Bratton, & Nation, 2005; Rocha, Valles, Hart, Bratton, & Nation, 2008; Valles, Rocha, Cardon, Bratton, & Nation, 2005) and cadmium (Cardon, Rocha, Valles, Bratton, & Nation, 2004) can also alter psychostimulant self-administration in adulthood after perinatal exposure.…”
Section: Discussionmentioning
confidence: 98%
“…This procedure has been used in previous developmental lead studies to ensure stable blood/tissue levels (cf. Nation et al, 2000;2003;Rocha et al, 2004). The present lead concentration was selected based on previous studies that found it produces differential behavioral effects while not altering dam body weights or the locomotor ability of pups (see Miller et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…This procedure has been used in our previous developmental lead studies to ensure stable blood/tissue levels (cf. Miller et al, 2000;Nation et al, 2000Nation et al, , 2003Rocha et al, 2004;Valles et al, 2005). The present lead concentration was selected based on previous investigations that found it produces differential behavioral effects while not altering dam weights or the locomotor ability of pups .…”
Section: Lead Exposurementioning
confidence: 99%
“…Procedures-Surgery was performed on test offspring at PND 60, which is a point demonstrated to be within the adult timeframe of behavioral change produced by developmental lead exposure (Miller et al, , 2001Nation et al, 2000Nation et al, , 2003. Using a backplate surgical procedure, implantation of chronic indwelling jugular catheters was performed using sterile techniques as described in detail elsewhere (Nation et al, 2003).…”
Section: Surgicalmentioning
confidence: 99%